Exercise-Induced Systemic Venous Hypertension in the Fontan Circulation - Navaratnam, Devaraj; Fitzsimmons, Samantha; Grocott, Michael; Rossiter, Harry B.; Emmanuel, Yaso; Diller, Gerard-Paul; Gordon-Walker, Timothy; Jack, Sandy; Sheron, Nick; Pappachan, John; Pratap, Jayant Nick; Vettukattil, Joseph J.; et al. (The American journal of cardiology, 2016)
Increasingly end-organ injury is being demonstrated late after institution of the Fontan circulation, particularly liver fibrosis and cirrhosis. The exact mechanisms for these late phenomena remain largely elusive. Hypothesizing that exercise induces precipitous systemic venous hypertension and insufficient cardiac output for the exercise demand, that is, a possible mechanism for end-organ injury, we sought to demonstrate the dynamic exercise responses in systemic venous perfusion (SVP) and concurrent end-organ perfusion. Ten stable Fontan patients and 9 control subjects underwent incremental cycle ergometry–based cardiopulmonary exercise testing. SVP was monitored in the right upper limb, and regional tissue oxygen saturation was monitored in the brain and kidney using near-infrared spectroscopy. SVP rose profoundly in concert with workload in the Fontan group, described by the regression equation 15.97 + 0.073 watts per mm Hg. In contrast, SVP did not change in healthy controls. Regional renal (p <0.01) and cerebral tissue saturations (p <0.001) were significantly lower and decrease more rapidly in Fontan patients. We conclude that in a stable group of adult patients with Fontan circulation, high-intensity exercise was associated with systemic venous hypertension and reduced systemic oxygen delivery. This physiological substrate has the potential to contribute to end-organ injury.